2013 6th International IEEE/EMBS Conference on Neural Engineering (NER) 2013
DOI: 10.1109/ner.2013.6696097
|View full text |Cite
|
Sign up to set email alerts
|

State and trajectory decoding of upper extremity movements from electrocorticogram

Abstract: Electrocorticography has been widely explored as a long-term signal acquisition platform for brain-computer interface (BCI) control of upper extremity prostheses. However, a comprehensive study of elementary upper extremity movements and their relationship to electrocorticogram (ECoG) signals has yet to be performed. This study examines whether kinematic parameters of 6 elementary upper extremity movements can be decoded from ECoG signals in 3 subjects undergoing subdural electrode placement for epilepsy surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…A first approach to integrate NC support into biomimetic kinematic decoders, namely post-processing, has been explored for both SUA/MUA (Aggarwal et al, 2013 ; Velliste et al, 2014 ) and ECoG signals (e.g., Wang et al, 2013b ) decoding. This consists in overwriting the output of the single kinematic model with null-velocity (neutral) estimates when a NC state is detected by a discrete NC/IC decoder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A first approach to integrate NC support into biomimetic kinematic decoders, namely post-processing, has been explored for both SUA/MUA (Aggarwal et al, 2013 ; Velliste et al, 2014 ) and ECoG signals (e.g., Wang et al, 2013b ) decoding. This consists in overwriting the output of the single kinematic model with null-velocity (neutral) estimates when a NC state is detected by a discrete NC/IC decoder.…”
Section: Discussionmentioning
confidence: 99%
“…It has since then provided users with MUA/SUA-based control over prostheses (Hochberg et al, 2012 ). It has additionally been applied for trajectory decoding from ECoG signals in online and offline studies (Pistohl et al, 2008 ; Kellis et al, 2012 ; Marathe and Taylor, 2013 ; Wang et al, 2013b ). KF applies to linear Gaussian state-space models (Bishop, 2006 ); that is, to state-space models with linear emission and transition models associated with Gaussian noises.…”
Section: Data-driven Decodersmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to decode neural activity are typically accomplished by training algorithms on tightly controlled experimental data with repeated trials. Much progress has been made to decode arm trajectories (Wang et al, 2012 ; Nakanishi et al, 2013 ; Wang et al, 2013a ) and finger movements (Miller et al, 2009 ; Wang et al, 2010 ), to control robotic arms (Yanagisawa et al, 2011 ; Fifer et al, 2014 ; McMullen et al, 2014 ), and to construct ECoG BCIs (Leuthardt et al, 2006 ; Schalk et al, 2008 ; Miller et al, 2010 ; Vansteensel et al, 2010 ; Leuthardt et al, 2011 ; Wang et al, 2013b ). Speech detection and decoding from ECoG has been studied at the level of voice activity (Kanas et al, 2014b ), phoneme (Blakely et al, 2008 ; Leuthardt et al, 2011 ; Kanas et al, 2014a ; Mugler et al, 2014 ), vowels and consonants (Pei et al, 2011 ), whole words (Towle et al, 2008 ; Kellis et al, 2010 ), and sentences (Zhang et al, 2012 ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Several studies have shown that arm and finger trajectories [1], [2], [3], [4], [5], [6], [7] can be decoded from ECoG signals. However, the performance of these decoders has been modest.…”
Section: Introductionmentioning
confidence: 99%